Designing a Comprehensive Evaluation Model of Educational Management in Elementary Schools of Lorestan Province: A Mixed-Methods Approach - Varmeziyari , Abolfazl; Hamidifar, Fatemeh; Khorshidi , Abbas; Shirzad Kebria , Baharak (Assessment and Practice in Educational Sciences, 2024)
The present study was conducted with the aim of designing a comprehensive evaluation model for educational management in elementary schools, with Lorestan Province as the case study. In terms of objectives, this research is applied, and in terms of data type, it follows an exploratory mixed-methods design (qualitative–quantitative). Regarding its nature and type, the qualitative phase adopts a grounded theory approach of the emergent type, while the quantitative phase is cross-sectional and survey-based. The statistical population in the qualitative section consisted of experts in the field of educational sciences, whereas in the quantitative section it included faculty members and principals of elementary schools in Lorestan Province, totaling 797 individuals (432 women and 365 men). The sampling method in the qualitative stage was purposeful theoretical sampling using the snowball technique, which reached theoretical saturation after interviewing 15 experts. In the quantitative phase, the sample size was determined using Morgan’s sampling table, resulting in 260 participants (141 women and 119 men). In this study, after conducting open and axial coding, the developed measurement tool was organized into a structured form and sent to the experts for selective coding and validation. Based on their feedback, a researcher-made questionnaire was finalized and distributed among the selected sample. The collected data were analyzed using descriptive and inferential statistics. Finally, the results led to the identification of two main dimensions—in order of priority: (1) individual and (2) organizational—as well as 14 components and 76 indicators for the comprehensive evaluation model of educational management in elementary schools (case study: Lorestan Province). The identified dimensions, integrated into a coherent framework, support the constructs of a unified concept referred to as the Comprehensive Evaluation Model of Educational Management in Elementary Schools (Lorestan Province Case Study).